Improvement in Refractory Iron Deficiency Anemia after Successful Eradication of H-Pylori - Aniq Fayyaz, Abid Ali, Rafia Wajid, Salman Javed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Helicobacter pylori has caused gastritis leading to bleeding and iron deficiency anemia. H-pylori eradication results in better response to oral iron treatment. Aim: To determine the frequency of improvement in refractory iron deficiency anemia after successful eradication of H-pylori. Study design: Descriptive, case series. Methodology: Patients (n=89) of refractory iron deficiency anemia, 15-55 years of either gender were included. After this taking relevant history, urea breath test was done for H-Pylori. After this, 10 days of PPI, bismuth, tetracycline and nitromidazole was given to the positive patients. Improvement in iron deficiency anemia was noted after 3 months of H-pylori eradication therapy. SPSS v.26 analyzed the data. Mean and standard deviation were calculated for age, duration of iron deficiency anemia and BMI. Stratification of improvement in refractory iron deficiency anemia was done with respect to age, gender and BMI. Post stratification Chi-Squire test was applied with P-value ≤0.05 was taken as significant. Results: Mean age was 35.90 ± 9.89 years. Improvement in refractory iron deficiency anemia after eradication of h pylori was found in 54 (60.67%) patients, whereas there was no improvement in 35 (39.33%) patients. Practical Implication: This study provided the local stats of the problem and helped the clinicians to design a protocol for eradication of H pylori in these particular patients thus improving refractory IDA. Conclusion: It was concluded that frequency of improvement in refractory iron deficiency anemia after eradication of H-pylori was very high. Keywords: H-Pylori, Eradication and Refractory Iron Deficiency Anemia.